Modelling the environmental conditions associated with megafires in Portugal - Purificação, Carolina (2022)
Numerical models represent an advanced technique used to better understand and evaluate the environmental conditions affecting fire development. This study starts with the largest forest fire occurred in Portugal in 2019. The fire burned an estimated total area of around 9,000 hectares in twelve hours. The Meso-NH atmospheric model is used to represent the local and mesoscale environment during this event. The model was configured in a single and large domain with 2500 m resolution, and a smaller domain with 500 m horizontal resolution. The simulations showed that the interaction between the Azores anticyclone and the Iberian thermal low produced an effect in wind intensity on the West coast of Portugal known as the Coastal low-level jet. The fire in Vila de rei county was characterized as a wind-driven fire due to this strong wind at surface. However, some forest fires generate pyrocumulonimbus clouds (PyroCb), the most dangerous and problematic environment to firefighting. Under this context, the Meso-NH model has been coupled to the fire propagation model (ForeFire) to study the development of pyro clouds.